2007
DOI: 10.1590/s0004-27302007000800006
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the diagnosis of Cushing's syndrome

Abstract: Among endocrine disorders, Cushing's syndrome (CS) is certainly one of the most challenging to endocrinologists due to the difficulties that often appear during investigation. The diagnosis of CS involves two steps: confirmation of hypercortisolism and determination of its etiology. Biochemical confirmation of the hypercortisolaemic state must be established before any attempt at differential diagnosis. Failure to do so will result in misdiagnosis, inappropriate treatment, and poor management. It should also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 73 publications
(134 reference statements)
0
46
0
5
Order By: Relevance
“…In light of this, physicians may be called to exclude the different forms of CS from the most common ones in the general population: obesity, depression, hirsutism, and metabolic syndrome (3). UFC collection and the 1 mg DST are simple, but neither is able to make a certain diagnosis of CS (15,20,21). The LNSC test, as proposed recently (5,6,7,10,11,12,14), is a reliable, noninvasive, stress-free, and low-cost procedure to diagnose CS.…”
Section: Discussionmentioning
confidence: 99%
“…In light of this, physicians may be called to exclude the different forms of CS from the most common ones in the general population: obesity, depression, hirsutism, and metabolic syndrome (3). UFC collection and the 1 mg DST are simple, but neither is able to make a certain diagnosis of CS (15,20,21). The LNSC test, as proposed recently (5,6,7,10,11,12,14), is a reliable, noninvasive, stress-free, and low-cost procedure to diagnose CS.…”
Section: Discussionmentioning
confidence: 99%
“…46 Some investigators have shown that elevated midnight salivary cortisol levels are a useful and simple screening test for hypercortisolism, with a sensitivity and specificity reaching 90% to 95%. 47 In patients without clearly diagnostic laboratory results, a classical DST (Liddle test: 2 mg/d oral dexamethasone for 2 days) may be performed.…”
Section: Glucocorticoid Secretionmentioning
confidence: 99%
“…Diagnosis of ACTH ectopic secretion involves two basic steps that cannot be omitted to prevent misdiagnosis: confirmation of hypercortisolism and determination of its etiology (differential diagnosis) (4). After confirmation of hypercortisolism in ACTH-dependent matter, bilateral sinus sampling (BIPSS) is the best single test to differentiate between a central and a peripheral source of ACTH (2,5).…”
Section: Introductionmentioning
confidence: 99%
“…Once EAS is confirmed, identification of the site of the primary tumor may begin with chest high-resolution computerized tomography (CT) scan. If results are normal, extensive abdominal CT should be carried out (4). In the case of negative scans, somatostatin receptor scintigraphy (SRS) or fluorine-18-fluorodeoxyglucose positron emission tomography scan ([18-F]-FDG-PET) may be used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation